Organisational Climate and the Work-related Learning of Employees - Kristinka Ovesni (AS: Andragoška Spoznanja)
The aim of this mixed methods research was to distinguish and to examine models of organisational climate regarding the work-related learning of employees. The theoretical rationale is found in the reflections of the learning supportive organisational climate as the main prerequisite of the process of participatory planning in adult education and learning, and as one of the core pillars in the process of building a learning organisation. For the purposes of triangulation and of complementarity, we adopted quantitative and qualitative methodology. The research was performed online from May to December 2018 and included employees from different companies in the Republic of Serbia. By using an explanatory sequential mixed methods research design with nested samples for the quantitative (Nqn=687) and the qualitative components (Nql=85), three models of organisational climate regarding the work-related learning of employees have been distinguished: the organisational climate of the fear of repression, the service-oriented organisational climate, and the learning supportive organisational climate.